The Morality of War : A Reader - Edited By Kinsella, David and Carr, Craig L. (New Delhi, India Viva Books, 2008)
The Morality of War surveys the fundamental principles and themes of the just war tradition through the words of the philosophers, jurists, and warriors who have shaped it.
Include Index
Keywords: War--Moral and ethical aspects -- Military ethics